-4(x+3)-7=4x+13

Simple and best practice solution for -4(x+3)-7=4x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+3)-7=4x+13 equation:


Simplifying
-4(x + 3) + -7 = 4x + 13

Reorder the terms:
-4(3 + x) + -7 = 4x + 13
(3 * -4 + x * -4) + -7 = 4x + 13
(-12 + -4x) + -7 = 4x + 13

Reorder the terms:
-12 + -7 + -4x = 4x + 13

Combine like terms: -12 + -7 = -19
-19 + -4x = 4x + 13

Reorder the terms:
-19 + -4x = 13 + 4x

Solving
-19 + -4x = 13 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-19 + -4x + -4x = 13 + 4x + -4x

Combine like terms: -4x + -4x = -8x
-19 + -8x = 13 + 4x + -4x

Combine like terms: 4x + -4x = 0
-19 + -8x = 13 + 0
-19 + -8x = 13

Add '19' to each side of the equation.
-19 + 19 + -8x = 13 + 19

Combine like terms: -19 + 19 = 0
0 + -8x = 13 + 19
-8x = 13 + 19

Combine like terms: 13 + 19 = 32
-8x = 32

Divide each side by '-8'.
x = -4

Simplifying
x = -4

See similar equations:

| n*5+8=7 | | (3z+1)=5+2 | | 2(r+h)-8=22 | | 2a+2=6-2a | | 0.03x+0.05(2500-x)=75 | | 5+22=n+16 | | 2(3x-1)=3-(-2-x) | | 3w+16=7w | | 12*x+6=-228 | | x*5+8=7 | | 8+2(8x-6)=16x+4 | | Xy+xz=1 | | f(x)=2x^2+12 | | 3x+32=56 | | 5(b+3)=3b+23 | | 3x-8=56 | | 4x+9-2x+2=3x-5-x | | 12-6x=2x+10 | | 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) |

Equations solver categories